Enhancement of redox stability and electrical conductivity by doping various metals on ceria, Ce1−xMxO2−δ (M = Ni, Cu, Co, Mn, Ti, Zr). (21st September 2015) - Myung, Jae-ha; Shin, Tae Ho; Huang, Xiubing; Carins, George; Irvine, John T.S.
Abstract Various metal oxide materials have been actively investigated to improve energy efficiency as exhaust-catalyst as well as electrodes in electrochemical devices such as fuel cells, ceramic sensors, photo-catalyst etc. Ceria-based materials are of great interest due to their wide applications; such as redox or oxygen storage promoter in automotive catalyst and solid state conductor in fuel cells. Here we report redox and electrical properties for Ce1−xMxO2−δ (M = Ni, Cu, Co, Mn, Ti, Zr) by X-ray diffraction (XRD) and simultaneous thermo-gravimetric analysis (TGA). Among various system, Ce1−xCuxO2−δ and Ce1−xNixO2−δ indicated relatively reversible redox behavior, although Cu2+ and Ni2+ had limited solid solubility in CeO2. The enhancement of oxygen carrier concentration and electrical conductivity as well as electrochemical activity in the ceria lattice by the introduction of small amounts transition metal cations have been considered in this study. Ce0.7Cu0.3O2−δ showed about 1015 μmol[O2]/g of oxygen storage capacity (OSC) with high redox stability at 700 °C. We also demonstrated that Ce0.9Ni0.1O2−δ was used as an anode of the YSZ electrolyte supported SOFC single cell; the maximum power density was 0.15 W/cm2 at 850 °C with hydrogen fuel.